Hearing Impairment Due to Cigarette Smoking and SimultaneousExposure to Occupational Noise - Mashallah Aghilinejad (Medical Journal of The Islamic Republic of Iran, 2010)
Background:Noise is the most common hazard in the workplace and noise induced hearing loss considered to be the most common occupational disease as well. Cigarette smoking, in some studies, has been known to induce hearing loss. The purpose of this study was to evaluate the effect of contemporary exposure to occupational noise and cigarette smoking on hearing.Methods:478 assembly workers of an automobile plant which were exposed tothe noise more than TLV (threshold limit value)level included in this study.After considering the exclusion criteria, all participants according to the smoking status were divided in smoker and nonsmoker groups and compared for hearing impairment.Hearing impairment in this study was assessed with the offered method of American Academy of Otolaryngology (AAO).   Results :Of 478 assembly workers, 225 persons were smokers and others non   smokers.Prevalence of hearing impairment in smokers was significantly higher (p<0.001). Hearing impairment had a significant relation with smoking status even after adjusting for cofounders like age and duration of work (OR=8.23, 95% CI=3.63-18.66).Conclusion:The results of this study suggested that cigarette smokers had more hearing impairment than non smokers. According to these results we concluded that in working environments, especially in noisy ones,workers must be encouraged to quit smoking and regular audiometric tests, especially for smokers,must be applied.We must consider not only the noise, but indeed all effective elements of hearing impairment in working environment that could compromise the hearing.